Small extracellular vesicles purification and scale-up - Zheng, Xinya; Ai, Hongru; Qian, Kewen; Li, Guangyao; Zhang, Shuyi; Zou, Yitan; Lei, Changhai; Fu, Wenyan; Hu, Shi (Frontiers in Immunology, 2024)
Exosomes are small extracellular vesicles (sEVs) secreted by cells. With advances in the study of sEVs, they have shown great potential in the diagnosis and treatment of disease. However, sEV therapy usually requires a certain dose and purity of sEVs to achieve the therapeutic effect, but the existing sEV purification technology exists in the form of low yield, low purity, time-consuming, complex operation and many other problems, which greatly limits the application of sEVs. Therefore, how to obtain high-purity and high-quality sEVs quickly and efficiently, and make them realize large-scale production is a major problem in current sEV research. This paper discusses how to improve the purity and yield of sEVs from the whole production process of sEVs, including the upstream cell line selection and cell culture process, to the downstream isolation and purification, quality testing and the final storage technology.